FAKTOR- FAKTOR YANG MEMPENGARUHI PENENTUAN HARGA JUAL BIBIT KAMBING PERANAKAN ETTAWA DI DUSUN NGANGGRING KECAMATAN TURI SLEMAN YOGYAKARTA - , CANDRA RATNANINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was aimed to estimated the selling price of Ettawa crossedbred and the purchasing price of feed, and also to identify the factors that influence the decision of selling price of Ettawa crossedbred. The location of the research was done in Nganggring Village Turi Sleman Yogyakarta. The research was done from July until August 2013. The sample taking was done towards the farmers and the sellers. The method of the sample taking was done through a purposive sampling with consideration the farmers that have Ettawacrossedbred 3 to 5 months old. The Samples of sellers taken 20 % of total sellers around 20 people. The descriptive data analysis to identify the selling price used table, while to identify factors that influence the decision of the selling price of the Ettawa crossedbred used a multiple linear regression analysis. The result of this research showed that the Ettawa crossedbred in male grade A at the age of 3 until 5month, has the highest selling price which is Rp. 1.729.730,00/head. The selling price of the kids in the cattle market is higher than the seller come directly to the pens. The result of the multiple linear regression analysis showed that the variable of the age and the goatâs grade positively and significantly influence the selling price of Ettawa crossedbred